2014
DOI: 10.1038/cddis.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Aurora-C interferes with the spindle checkpoint by promoting the degradation of Aurora-B

Abstract: The chromosomal passenger complex (CPC) plays a pivotal role in controlling accurate chromosome segregation and cytokinesis during cell division. Aurora-B, one of the chromosomal passenger proteins, is important for the mitotic spindle assembly checkpoint (SAC). Previous reports noted that Aurora-C is predominantly expressed in male germ cells and has the same subcellular localization as Aurora-B. Increasing evidence indicates that Aurora-C is overexpressed in many somatic cancers, although its function is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Given the fact that loss of Aurora kinase activity can also induce premature anaphase onset, 32,35 and that H3T3-P is a prerequisite for Aurora C localization to the ICA in mouse oocytes, 14 we attribute the defects of SAC to loss of Aurora C function, which is consistent with the idea that H3T3-P-dependent Aurora CPC function plays a role in SAC activation through phosphorylating and targeting SAC proteins to the kinetochore region. 15,29,32,36 Consistent with recent published data, 14 we observed a delay in anaphase onset in oocytes, even after 17 h incubation, when 5-ITu was administered from the early meiotic stages, either GV or GVBD, that may be due to the fact that chromatin was not fully condened into typical chromosome structure. We tend to believe that different drug application time produces different effects, suggesting H3T3-P regulates meiotic progression at multi steps.…”
Section: Discussionsupporting
confidence: 90%
“…Given the fact that loss of Aurora kinase activity can also induce premature anaphase onset, 32,35 and that H3T3-P is a prerequisite for Aurora C localization to the ICA in mouse oocytes, 14 we attribute the defects of SAC to loss of Aurora C function, which is consistent with the idea that H3T3-P-dependent Aurora CPC function plays a role in SAC activation through phosphorylating and targeting SAC proteins to the kinetochore region. 15,29,32,36 Consistent with recent published data, 14 we observed a delay in anaphase onset in oocytes, even after 17 h incubation, when 5-ITu was administered from the early meiotic stages, either GV or GVBD, that may be due to the fact that chromatin was not fully condened into typical chromosome structure. We tend to believe that different drug application time produces different effects, suggesting H3T3-P regulates meiotic progression at multi steps.…”
Section: Discussionsupporting
confidence: 90%
“…AURKB localizes with microtubules of meiotic spindles ( Balboula and Schindler, 2014 ) and likely comes into close proximity to kinetochores and can regulate recruitment of SAC components like MAD2 ( Figure 5 ). When both AURKs are present, AURKC may suppress or displace AURKB activation of the SAC, as previously seen in mitotic cells with overexpression of AURKC, resulting in reduced CPC expression and weakened AURKB activity ( Lin et al , 2014 ). Only in the absence of AURKC can AURKB activate the SAC ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 55%
“…Despite their similarities in the protein structure and cellular localization at chromosome passenger complex, AurkC displayed unique characteristics different from AurkB. Lin et al showed that in cancer cells, overexpression of AurkC could displace AurkB from centromere and impaired SAC function (Lin et al, 2014 ). Our previous results also showed that high level AurkC in mouse oocytes accelerated securin degradation, caused chromosome mis-alignment and cytokinesis failure (Sharif et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…AurkC is a mammalian specific Aurora kinase closely related to AurkB (Carmena and Earnshaw, 2003 ; Lin et al, 2014 ; Sasai et al, 2004 ). It is specially highly expressed in mammalian gamete and required for spermatocyte meiosis (Dieterich et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%